KEPUASAN PENGUNJUNG DALAM RANGKA PENGEMBANGAN OBJEK WISATA DI KABUPATEN KEDIRI TAHUN 2016 - Widyatmoko, Sardjono, Setyawan, Sigit, Sardjono, Moch Haris (Universitas Nusantara PGRI Kediri, 2016)
ABSTRACTImproved service and repair facility must be done so that visitors do not get bored for a return visit, because if the services and facilities of a tourist attraction well then the visitors will come back to visit these attractions. Tourism Object potential to attract visitors in Kediri very much. Sightseeing in Kediri district were: Tegowangi Temple, Temple Surowono, Simpang Lima Gumul, Kelud, Ubalan, Niagara Irenggolo, Petilasan Sri Aji Joyoboyo, and The Old Church Puhsarang. This method is a method that can be used to understand the object that becomes the problem. Judging from the existing problems and objectives, this study classified as survey research is